Nghiên cứu chế tạo vật liệu polyme compozit trên cơ sở nhựa nền polyeste không no và silicafum. Phần I. Cấu trúc và tính chất vật liệu polyme compozit trên nền nhựa polyeste không no và silicafum khi chưa có chất liên kết - Đạt, Trịnh Minh; Chương, Bùi; Phúc, Bạch Trọng; Nhung, Nguyễn Thị Phương (Vietnam Journal of Chemistry, 2012)
Ortho unsaturated polyester/silicafume composite were prepared by high rate mixing with unchangeable temperature, then using ultrasound wave and vacuum to eliminate bubbles. Dispersion of the silicafume was characterized by viscosity, SEM and TGA. The results showed that viscosity of composition and dispersion level of silicafume depend on time and speed of mixing. The best mechanical properties were obtained at silicafume content 1.5 wt%.